2020
DOI: 10.1016/j.annemergmed.2020.06.019
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Changes in Emergency Department Visits After a State Declaration During the Time of COVID-19

Abstract: Study objective: In the initial period of the coronavirus disease 2019 (COVID-19) pandemic, there has been a substantial decrease in the number of patients seeking care in the emergency department. A first step in estimating the impact of these changes is to characterize the patients, visits, and diagnoses for whom care is being delayed or deferred. Methods:We conducted an observational study, examining demographics, visit characteristics, and diagnoses for all ED patient visits to an urban level 1 trauma cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
131
3
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(161 citation statements)
references
References 7 publications
24
131
3
3
Order By: Relevance
“…While in some clinical situations we observed a persistent decrease throughout the lockdown period, in others (psychiatric conditions, thoracic pain, acute coronary syndrome, atrial fibrillation, hand wounds, head trauma, headaches, abdominal pain, renal colic, urinary tract infection, acute diabetes decompensation/diabetes acid ketosis, and appendicitis) we observed a secondary increasing trend but without reaching the expected values. As has been reported, our data indicate that patients may have delayed ED visits [7][8][9][10][11] and access to emergency surgical care [11], even for conditions that might have required hospitalization, including ICU. If for traumatic pathologies we can assume a reduction of their frequency during the lockdown period, this does not seem credible for the other clinical conditions.…”
Section: Discussionsupporting
confidence: 76%
“…While in some clinical situations we observed a persistent decrease throughout the lockdown period, in others (psychiatric conditions, thoracic pain, acute coronary syndrome, atrial fibrillation, hand wounds, head trauma, headaches, abdominal pain, renal colic, urinary tract infection, acute diabetes decompensation/diabetes acid ketosis, and appendicitis) we observed a secondary increasing trend but without reaching the expected values. As has been reported, our data indicate that patients may have delayed ED visits [7][8][9][10][11] and access to emergency surgical care [11], even for conditions that might have required hospitalization, including ICU. If for traumatic pathologies we can assume a reduction of their frequency during the lockdown period, this does not seem credible for the other clinical conditions.…”
Section: Discussionsupporting
confidence: 76%
“…It is also certainly possible that some portion of care usually provided in the ED was occurring in other settings, such as through telemedicine consultations. As others have noted [10], however, it is unlikely that all of the declines observed can be attributed to a decrease in actual incidence of disease or a shift in care settings, particularly for the more severe disease states requiring procedures. Our findings therefore echo others' concerns that some patients avoided care for emergency conditions that likely warranted expedient care during the COVID-19 surge.…”
Section: Discussionmentioning
confidence: 86%
“…Nearly 60% of respondents also expressed concerns about not being able to have a visitor or guest present during their care in the ED. A number of studies have indeed shown decreased ED visits in the U.S. and other parts of the world during the COVID-19 surge, including reduced presentations of acute coronary syndromes and strokes [4][5][6][7][8][9][10][11]. An additional study found evidence of increased rates of out-of-hospital cardiac arrests, likely due to delays in care [12].…”
Section: Introductionmentioning
confidence: 99%
“…There are scant data regarding the change in volumes and triage acuity of patients presenting to emergency departments (EDs) prior to and after COVID-19. A recent single-center report at an urban hospital in the United States reported a 35% decline in ED visits compared with the previous year (3). A reduction in volumes, particularly among those with severe acute conditions, may lead to a higher rate of complications and higher mortality in the general population.…”
Section: Introductionmentioning
confidence: 99%